Workshop Pembuatan Media Ajar Berbasis Augmented Reality di Yayasan Perguruan Mamiyai Al-Ittihadiyah Medan - Zufria, Ilka; Nasution, Yusuf Ramadhan; Suhardi (Jurnal Pengabdian Masyarakat, 2023)
Information technology has developed very rapidly and covers various fields. The education sector is one area that is influenced by information technology. Both in the formal learning process at school and non-formal in the form of training outside of school. The form of participation from universities, especially the Computer Science study program FST UIN North Sumatra Medan in this community service activity is providing skills training in the field of Augmented Reality to create learning media for teachers at the Mamiyai Al-Ittihadiyah Medan College Foundation. The activity was held with the theme "Workshop on Making Teaching Media Based on Augmented Reality.